Investigations on the Berezan Island, 2006–2013 (Hermitage Museum Archaeological Mission) - Chistov, Dmitrij (Hyperboreus, 2015)
A survey of the excavations on the Berezan Island (the estuary of Dnepr and S. Bug) conducted by the Hermitage Museum Archaeological Mission in 2006–2013.